Propriedades eletrônicas e estruturais de nanoestruturas de dióxido de titânio por primeiros princípios - Andre Alves Lino (2013)
In this work, we applied rst principles calculations based on the Density Functional Theory (DFT) to study electronic and structural properties TiO2 nanostructures. We considered two main problems: The characterization of edge states in nanoribbons and description of the ground state electronic structure of TiO2 nanosurfaces interacting with carbon nanostructures. For the rst problem, we showed that edge states are found as gap states or dening the bottom of the conduction band. We also found that, by doping with electrons, a process which is facilitated by the high work function of the material, a half-metallicity phenomenology arises, with a single spin component conduction along the edges. We explained the stability of the charged edge states in terms of a U-negative model. For the second problem, we investigated the interaction of TiO2 nanostructured surfaces with carbon nanomaterials (nanotubes and graphene). In a first approach, we used the DFT formalism with an exchange-correlation functional parametrized within the generalized gradient approximation. As a result, we found that the simple deposition of these nanostructures, one on top of the other, leads to a charge transfer between the subsystems. In a second approach, we used the DFT+U method, which gives a better description of the interaction between the most localized electrons belonging to titanium atoms. Applied to the hybrid TiO2-carbon materials, the DFT+U approach showed that such systems may improve the TiO2 photocatalysis processes eciency since the description of the ground state is consistent with the idea of spatial separation of the phote generated electron-hole pair.